On the Measurement of Multi-component T2 Relaxation in Cartilage by MR Spectroscopy and Imaging - Zheng, ShaoKuan (2010)
The multi-component T(2) relaxation in bovine nasal cartilage (BNC) was investigated by NMR spectroscopy using the CPMG sequence and microscopic MRI (μMRI) method using a CPMG-SE imaging sequence. All experimental data were analyzed by the non-negative least square (NNLS) procedure. Only one T(2) component was found in BNC by both experimental methods (about 113 ms and 170 ms before and after being enzymatically digested by trypsin). Several experimental and specimen-related factors were investigated in this study and it was found that some of them could produce artificial multi-component T(2), including the use of the standard MSME imaging sequence at certain imaging gradients.